Rotor-Bearing System Stability Performance Comparing Hybrid versus Conventional Bearings - Gomez-Mancilla Julio; Nosov Valeri; Silva-Navarro Gerardo (International Journal of Rotating Machinery)
New closed-form expressions for calculating the linear stability thresholds for rigid and flexible Jeffcott systems and the imbalance response for a rotor supported on a hybrid bearing are presented. For typical bearings characteristics, expressions yield stability thresholds practically equal to those reported by Lund (1966). The hybrid bearing design has a single injection port whose location is so chosen to stabilize the bearing performance and to reduce the steady equilibrium attitude angle. Rotordynamics coefficients graphs for conventional and pressurized bearings, as functions of bearing equilibrium eccentricity and/or Sommerfeld number, are presented. Using the rotordynamics coefficients into the expressions for the corresponding velocity thresholds and the imbalance response, the system stability and vibration performances are estimated and analyzed. When comparing the Jeffcott flexible shaft supported on two journal bearings of the conventional type with the hybrid type, the results show a clear superiority of the pressurized design as far as stability behavior is concerned. Specifically for cases of flexible shafts with similar characteristics to those used in industry, the analysis shows that this design yields velocity thresholds 25%–40% higher compared to the conventional circular ones. Also this bearing displays nonlinear feeding pressure behavior, and it is capable of reducing the synchronous vibration amplitude in most speed ranges, except around the critical speed; moreover, for certain Jeffcott configurations the amplitude reduction can be substantial.